Developing a Global Strategy for strengthening the occupational therapy workforce: a two-phased mixed-methods consultation of country representatives shows the need for clarifying task-sharing strategies - Sutanuka Bhattacharjya; Sarah Curtis; Supakorn Kueakomoldej; Claudia von Zweck; Giuliano Russo; Karthik Mani; Sureshkumar Kamalakannan; Ritchard Ledgerd; Tiago S. Jesus; World Federation of Occupational Therapists (Human Resources for Health, 2024)
Abstract Introduction Occupational therapy has been underdeveloped and often neglected in the global health workforce agenda, contrasting with the global rise of population needs for services. The World Federation of Occupational Therapists (WFOT) is utilizing a research-based, multi-step process for developing a Global Strategy for strengthening the occupational therapist workforce. A multi-pronged scoping review, situational analysis, and expert input process enabled the drafting of a provisional Global Strategy. Here, feedback on that draft from representatives of WFOT member organizations was obtained and analyzed as one key intermediate step toward shaping the in-developing Strategy’s content and structure. Methods Two-phased, mixed-methods consultation consisting of: (1) online survey with score ratings and comments on the utility of each strategy and (2) four in-person focus groups discussions on low-scoring items involving a total of 76 representatives of WFOT member organizations. The focus group discussions were analyzed using an inductive thematic analysis approach. Results Strategies involving ‘task shifting/task sharing’ or the ‘harmonization of workforce data-collection requirements’ received the lowest scores in the initial survey and were thereby addressed in the focus groups discussions. The overarching theme of the focus groups was the need to: “clarify, specify, and contextualize the strategies”, including: (1) “clarify the terminology and specify the application”, for example, describe the meaning of task shifting, specify which tasks can (and cannot) be shifted and to whom, to address concerns regarding scope-of-practice, service demand, and safety; and (2) “outline the context of need and the context for the implementation” of the strategies, elucidating why the strategies are needed and how they can be feasibly implemented across the different jurisdictional contexts. Conclusion Within a mixed-methods consultation, WFOT representatives identified challenging topics on the draft workforce strategies and suggested methods to improve the Global Strategy, its acceptability, and implementation. The terms ‘task shifting/task sharing’ raised the greatest discussion among the profession leaders, when the strategy was not sufficiently clarified, specified, or contextualized.